Maize variety preferences among smallholder farmers in Ethiopia: Implications for demand-led breeding and seed sector development - Marenya, Paswel Phiri; Wanyama, Rosina; Alemu, Solomon; Westengen, Ola T.; Debello, Moti Jaleta (2022)
Among smallholder maize farmers in Ethiopia (and similar areas in Africa), yield and stress tolerance traits in maize varieties are important. While high yields remain a major objective, breeding and seed system development programs are increasingly based on the recognition that farmers also have an interest in other agronomic and consumption traits. In this paper we illustrate these issues by measuring the trade-offs farmers may be willing to make for specific traits in the mid-altitude maize markets in Ethiopia. Based on Choice Experiments among 1499 respondents, we estimate the preference for a set of agronomic and consumption traits relative to yield. by capturing farmers’ “willingness to sacrifice yield”. The results suggest a significant willingness to sacrifice yield for drought tolerance among both male and female household members, but not for early maturity per se. There was also a high willingness to sacrifice yields for plant architecture traits like closed tip and lodging resistance among male participants, but not among females. Heterogeneity in responses according to gender, education and land area under maize cultivation suggests that market segmentation is necessary for seed system development to become more demand-led and inclusive. Final and realistic segmentation will depend on the commercial viability or social impact potential of each segment.